Tuberous Sclerosis Complex Presenting as Periungual Fibromas: A Rare Case Report and Literature Review - Li Y; Wang Z; Yang Y; Xu X (Clinical, Cosmetic and Investigational Dermatology)
Ying Li,1,* Zhipeng Wang,1,* Yanhua Yang,2 Xiaoyan Xu3 1Department of Pathology, Sanya Central Hospital (The Third People’s Hospital of Hainan Province), Sanya, 572000, People’s Republic of China; 2Department of Pathology, Qingdao Municipal Hospital, Qingdao, 266071, People’s Republic of China; 3Department of Pathology, College of Basic Medicine of Inner Mongolia Medical University, Hohhot, Inner Mongolia, 010059, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Li, Department of Pathology, Sanya Central Hospital (The Third People’s Hospital of Hainan Province), No. 1154, Jiefang Road, Tianya District, Sanya, 572000, People’s Republic of China, Tel +86-898-38225602, Email liying91588@163.com Xiaoyan Xu, Department of Pathology, College of Basic Medicine of Inner Mongolia Medical University, No. 1, Tongdao North Street, Huimin District, Hohhot, Inner Mongolia, 010059, People’s Republic of China, Tel +86-471-3451545, Email xxyfpc@126.comBackground: Tuberous sclerosis complex (TSC) is a rare autosomal-dominant disorder involving multiple organs including skin, brain, heart, lung, kidney and liver. It usually occurs as early as birth or even in utero, with rare cases diagnosed in their adulthood. Here, we present a rare adult case of TSC presenting as periungual fibromas (PF).Case Presentation: A 67-year-old gentleman showed recurrence of multiple periungual polypoid tumors on all the toes of the right foot when presenting to our department. On physical examination, there were polypoid and verrucous protrusions on the nail fold side of the proximal toe. Computed tomography scan indicated multiple subependymal nodules and renal cyst. Pathological analysis for the polypoid tissues showed fibroepithelial-like lesions, epidermal hyperkeratosis, and acanthosis. Therefore, the patient was diagnosed with TSC presenting as PF.Conclusion: We reported a rare case of TSC diagnosed in the adulthood based on the presence of PF, subependymal nodules, and renal cyst.Keywords: tuberous sclerosis complex, periungual fibromas, renal cyst, subependymal nodule